Anti-Inflammatory, Antithrombotic, and Antioxidant Properties of Amphiphilic Lipid Bioactives from Shrimp - Alexandros Tsoupras; Paschalis Cholidis; Dimitrios Kranas; Evangelia Aikaterini Galouni; Anna Ofrydopoulou; Pavlos Efthymiopoulos; Katie Shiels; Sushanta Kumar Saha; George Z. Kyzas; Chryssa Anastasiadou (Pharmaceuticals)
Background/Objectives: Marine organisms, including shrimps, have gained research interest due to containing an abundance of bioactive lipid molecules.This study evaluated the composition and the in vitro biological activities of amphiphilic bioactive compounds from four different wild shrimp species: Litopenaeus vannamei, Penaeus kerathurus, Aristaeomorpha foliacea, and Parapenaeus longirostris. Methods: Total lipid (TL) extracts were obtained from shrimp and separated into total amphiphilic (TAC) and total lipophilic (TLC) compounds. Phenolic (TPC) and carotenoid (TCC) contents, antioxidant activities (DPPH, ABTS, FRAP assays), and biological effects on platelet-activating factor (PAF) and ADP-induced platelet activation were evaluated. Structural analyses were performed using ATR-FTIR spectroscopy, while LC-MS was used to elucidate the fatty acid composition and overall structure of polar lipids (PLs) present in shrimp TAC extracts. Results: TAC extracts, rich in phenolics, carotenoids, PL, and unsaturated fatty acids (UFAs), exhibited stronger anti-inflammatory and antithrombotic activities compared with TLC extracts, which showed potent antioxidant capacity. Significant amounts of UFAs, such as the monounsaturated fatty acid (MUFA) oleic acid (C18:1n9) and omega-3 (n3) polyunsaturated fatty acids (PUFAs) like eicosapentaenoic acid (EPA; C20:5n3) and docosahexaenoic acid (DHA; C22:6n3), were detected in the PLs of shrimp TAC extracts, with favorable anti-inflammatory values for their n6/n3 PUFA ratio. Shrimp amphiphilic bioactives present in the TAC extracts provide anti-inflammatory effects against the PAF pathway and antithrombotic effects against ADP and eicosanoid pathways. Conclusions: The overall findings support further study on the use of shrimp extracts rich in anti-inflammatory, anti-thrombotic, and antioxidant amphiphilic bioactives as ingredients to produce new bio-functional health-promoting products, in the context of sustainable development and circular economy.